LANDASAN PENGEMBANGAN KURIKULUM DALAM KOMPONEN TUJUAN PEMBELAJARAN PAI - ., Marjuni (Inspiratif Pendidikan, 2018)
Abstract: Curriculum is a very decisive component in an educational system, therefore the curriculum is a tool to achieve the educational system, therefore the curriculum is a tool to achieve the goals of education and also as a guide in the implementation of teaching on all types and levels of education. The curriculum is one of the tools to achieve the goal of education, which is to improve the quality of Indonesian people, ie human beings who believe and be cautious to God Almighty, morality, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible . The foundation for the development of the PAI curriculum is essentially the factors that should be considered and considered by the curriculum developers when they want to develop or plan a curriculum of educational institutions. The main principles in developing PAI curriculum are theological, philosophical, psychological, sociocultural, and technology